Influence of intrinsic factors of cowpea seed varieties on the cowpea weevil, Callosobruchus maculatus (Coleoptera: Chrysomelidae) - Temitope E. Arotolu; Joseph A. Adeyemi; Chris O. Adedire (Journal of Crop Protection, 2018)
In this study, the roles of proximate composition, mineral profile and heavy metal contamination were investigated on selected biological activities of Callosobruchus maculatus (F.) that were maintained on six cowpea cultivars. The levels of heavy metals; cadmium, lead and arsenic in six cowpea cultivars; Ife Brown, Ife BPC, Oloyin, Drum, Sokoto Local, and Niger White were determined by atomic absorption spectrophotometry while those of nutrient elements; zinc, sodium, calcium and potassium were determined using flame photometry. The proximate analyses and physico-chemical characterization of the cowpea cultivars were also performed. Callosobruchus maculatus was maintained on the cowpea cultivars and biological activities such as oviposition, adult emergence, percentage seed damage, and weight loss were monitored. The levels of heavy metals, mineral elements and proximate composition differed significantly among the cultivars investigated, and the values were comparable to those reported for cowpea cultivars in other studies. Of the cowpea cultivars, the Ife Brown was the most susceptible to the bruchid C. maculatus infestation while the Drum cultivar was the least susceptible. In conclusion, the results from this study show that the cowpea cultivars differed in the levels of toxic and mineral elements. While there were significant relationships between physical parameters (e. g. seed hardness), proximate composition (moisture contents and crude fibre) and adult emergence and oviposition, there was no strong evidence that the levels of heavy metals and mineral elements play significant role on the biology of C. maculatus.